A complexity perspective on innovation processes for subsea technology development. (16th April 2009) - Aasen, Tone Merethe Berg
In today's business thinking, innovation is commonly equated with progress, indicating an underlying assumption that company management have the power to choose a specific future and control the way into it. Drawing on examples from a longitudinal research initiative in the Norwegian petroleum company StatoilHydro, this article raises some of the problems with this thinking. Experiences from the study indicate that most people in the organisation do not consider what they do in their everyday organisational life as 'innovation', but rather as the provision, testing and use of technology. This suggests that the recognition of everyday activity as acts of innovation is an emergent phenomenon, expressed and potentially idealised in retrospection. The importance ascribed to technology as the enabler of a chosen future also makes topical the conceptualisation of 'technology' in terms of innovation.